Financial Performance and Business Sustainability Through Financial Literacy and Inclusion Among East Java MSME Actors - Maria Widyastuti; Deograsias Yoseph Yustinianus Ferdinand; Margaretha Zhilla Natasya Kunang (International Journal of Applied Business and International Management, 2025)
Indonesia’s MSME sector remained resilient during the crisis, boosting post-crisis GDP and employment. This study focuses on MSMEs in Malang, Jember, and Surabaya, addressing the limited financial literacy and financial inclusion that hinder MSME actors from utilizing financial services effectively. Using purposive sampling, data were collected from 290 respondents and analyzed using Partial Least Squares (PLS). The results show that financial literacy significantly affects financial performance (? = 0.367, p = 0.034) and business sustainability (? = 0.242, p = 0.039). Financial inclusion also has a significant impact on financial performance (? = 0.324, p = 0.036) and business sustainability (? = 0.214, p = 0.018). Financial performance strongly influences business sustainability (? = 0.661, p = 0.000). Indirectly, financial literacy influences business sustainability through financial performance (? = 0.214, p = 0.034), as does financial inclusion (? = 0.242, p = 0.018). These findings confirm that improving financial literacy and inclusion enhances financial performance, which in turn ensures the long-term continuity of MSMEs. Interventions such as targeted financial education and improved access to financial services are vital to strengthening MSME sustainability